Diversity of arboreal insects in the Tagur Tinggi Waterfall Area Lempake District, Samarinda, East Kalimantan - Hariani, Nova; Fudiantoro, Aldi; Patang, Fatmawati; Yuliatin, Ervinda; Budiman, Budiman (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2026)
The Tagur Tinggi Waterfall region is characterized by its verdant and expansive landscape, featuring diverse flora such as trees and grass. This region is optimal for arboreal insects as a habitat. Arboreal insects, which are abundant and readily seen, inhabit the upper branches of trees and travel between trees to facilitate pollination. The abundance of arboreal insects serves as a reliable measure of the overall well-being of an ecosystem. The present study aims to identify the various species of insects that inhabit the trees in the Tagur Tinggi region and calculate the diversity, evenness, and dominance measures for these arboreal insects. This study used the transect approach, wherein samples are gathered bi-daily in the morning and evening. There were a total of 44 bug species belonging to 19 different families and 8 distinct orders. The arboreal insect diversity index (H') was measured to be 3.24 in the morning and 3.14 in the afternoon. Arboreal insects have an evenness index (E) of 0.91 during the morning and 0.87 during the afternoon. Additionally, they have a dominance index (D) of 0.044 in the morning and 0.056 in the afternoon. According to the health index values obtained, it can be inferred that the Tagur Tinggi Waterfall area in Lempake Samarida Village is highly conducive to the survival of arboreal insects. This is due to the well-preserved habitat and abundant vegetation structure that supports the life of arboreal insects.